Planar Hyperspectral Imager With Small Smile and Keystone Based on Two Metasurfaces - Jiadong Zhao; Weijie Kong; Changtao Wang; Mingbo Pu; Jinjin Jin; Xiaoliang Ma; Xiong Li; Xiangang Luo (IEEE Photonics Journal, 2022)
Metasurfaces, which are ultrathin planar artificial materials flexibly controlling the phase, amplitude, and polarization of the light, have facilitated the high integration and miniaturization of hyperspectral imaging systems. However, the pushbroom hyperspectral imaging systems based on metasurfaces usually face the large smile and keystone, which reduces the spectral uniformity and the fidelity of the spectral information. Moreover, the employment of many metasurfaces would cause manufacturing difficulties. In this paper, a planar hyperspectral imager only using two metasurfaces is proposed to achieve a spectral resolution of 3.5 nm in 850-1000 nm band with the near diffraction-limited focusing capability, and its maximum of smile and keystone reach to 124.4 μm and 33.6 μm for the image plane size of 4.75 mm × 1.35 mm and pixel size of 26 μm × 26 μm, respectively. This imager can provide a promising avenue for portable environmental monitoring systems and wearable electronic consumer products.